Advances in conceptual modeling : ER 2016 Workshops, AHA, MoBiD, MORE-BI, MReBA, QMMQ, SCME, and WM2SP, Gifu, Japan, November 14-17, 2016, Proceedings /: ER 2016 Workshops, AHA, MoBiD, MORE-BI, MReBA, QMMQ, SCME, and WM2SP, Gifu, Japan, November 14-17, 2016, Proceedings. (2016) - Unknown
No abstract available